2007
DOI: 10.1038/sj.bjc.6603773
|View full text |Cite
|
Sign up to set email alerts
|

Epirubicin–vinorelbine vs FEC100 for node-positive, early breast cancer: French Adjuvant Study Group 09 trial

Abstract: The aim of the study was to compare our reference adjuvant chemotherapy, FEC100 (fluorouracil 500 mg m −2 , epirubicin 100 mg m −2 and cyclophosphamide 500 mg m −2 , six cycles every 21 days), to an epirubicin–vinorelbine (Epi-Vnr) combination for early, poor-prognosis breast cancer patients. Patients (482) were randomised to receive FEC100, or Epi-Vnr (epirubicin 50 mg m −2 day 1 and vinorelbine 25 mg m −2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…Other single agents were compared with or without vinorelbine in three trials . Nine trials compared vinorelbine‐combined chemotherapy with other regimens .…”
Section: Resultsmentioning
confidence: 99%
“…Other single agents were compared with or without vinorelbine in three trials . Nine trials compared vinorelbine‐combined chemotherapy with other regimens .…”
Section: Resultsmentioning
confidence: 99%
“…Of 441 potentially relevant abstracts identified, 98 papers met full inclusion criteria: follow-up modalities were reported in 66 RCTs [ 31 - 95 ] while no information was given in the remaining 32 [ 96 - 127 ]. Two different trials, the ABCSG trial 8 and ARNO 95 trial, are reported in the same paper by Jakesz et al [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given that weekly paclitaxel and 3-weekly docetaxel are likely to yield comparable results, it is worth noting that no clinically relevant benefit was obtained by sequencing 4 courses of 3-weekly docetaxel with 4 cycles of 5-fluorouracil, epirubicin and cyclophosphamide (FEC) compared to either 8 cycles of FEC or 4 cycles of epirubicin followed by 4 CMF cycles in a recent UK trial [25]. Only one trial has previously investigated the role of vinorelbine in the adjuvant treatment of breast cancer [26]. This trial compared 6 cycles of epirubicin and vinorelbine versus 6 cycles of FEC-100 and gave comparable results.…”
Section: Discussionmentioning
confidence: 99%